Developing sustainable management strategies for the Floating Market tourism area in Lembang - Simorangkir, Cavin Ornando (School of Tourism, Universitas Ciputra Surabaya, 2024)
This research aims to develop strategies for managing the Floating Market tourism area in Lembang, West Bandung Regency (KBB), focusing on sustainable resource management. Utilizing qualitative methods, data were collected through in-depth interviews with key stakeholders, including the Floating Market tourism manager, worker groups, local residents, and the KBB Tourism and Culture Agency. The research employs SWOT analysis integrated with IFAS-EFAS matrices to develop strategies based on critical issues identified, such as employees earning below the minimum wage (UMR), inadequate contributions to public facilities, limited collaboration with local communities and government, insufficient employee training, and non-transparent recruitment processes. The research results propose several strategies, including adjusting wages to competitive levels, implementing regular employee training programs, and enhancing contributions to public facility improvements. Additionally, the research emphasizes the importance of strengthening collaboration with local communities, government, and relevant agencies, as well as increasing local residents’ involvement in management and ensuring transparency in recruitment process. This research highlights the significance of sustainable tourism development theory in balancing economic, environmental, and social factors for long-term success. By integrating a comprehensive resource management plan, the floating market can preserve the environment, improve public facilities or infrastructure, enhance food security with local products, and undertake other efforts. These initiatives contribute to a resilient tourism model that aligns with regional development goals. Overall, these findings provide a strategic model for similar attractions, demonstrating how to balance growth and sustainability while fostering positive relationships between tourism and local development.